The search The continuning story of the Tracker - Brown, Tom (Jr.); Owen, William (Prentice-Hall, Inc. Englewood Ciffs, New Jersey, 1980)
Continuing an account that began with The Tracker, Brown discusses his adventures in the wilderness, detailing how the year he spent living alone in the woods with nothing but a knife was a path to self-discovery
Keywords: Tracking and trailing; Nature